2008
DOI: 10.1111/j.1556-4029.2008.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Falls and Blows in Blunt Head Trauma: Systematic Study of the Hat Brim Line Rule in Relation to Skull Fractures

Abstract: In the discrimination of falls from blows in blunt head trauma, the hat brim line rule is one of the most often used criteria. The present study assesses the validity of the hat brim line rule for skull fractures and looks at other possible criteria. All autopsy cases were retrospectively analyzed on a 5‐year period. Cases selected consisted of downstairs falls (n = 13), falls from one’s own height (n = 23), and homicidal blows (n = 44). Results show that fractures above the hat brim line are more in favor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 2 publications
3
84
1
3
Order By: Relevance
“…Given the predominance of righthandedness, they are mostly on the left side (59,61). The depressed injury of Maba 1, plus those of Dolní V estonice 11/12, Qafzeh 11, and Shanidar 1 (and possibly Krapina 34.7 and Cova Negra 1), therefore generally conforms to the pattern of lesions from interindividual aggression among recent humans.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Given the predominance of righthandedness, they are mostly on the left side (59,61). The depressed injury of Maba 1, plus those of Dolní V estonice 11/12, Qafzeh 11, and Shanidar 1 (and possibly Krapina 34.7 and Cova Negra 1), therefore generally conforms to the pattern of lesions from interindividual aggression among recent humans.…”
Section: Discussionmentioning
confidence: 54%
“…Cranial injuries from recent human interpersonal altercations are primarily facial (40) and otherwise mostly occur above the "hat brim line" (59,60). Given the predominance of righthandedness, they are mostly on the left side (59,61).…”
Section: Discussionmentioning
confidence: 99%
“…Cranial trauma, especially fractures of the vault bones, is often used as evidence of interpersonal violence among past populations (Walker, 2001), but distinguishing intentional trauma from accidental trauma requires a more critical interpretive approach (Andrushko and Torres, 2011;Kremer et al, 2008).…”
Section: Etiology -Violent or Accidental Traumamentioning
confidence: 99%
“…5 Several authors 59e65 have suggested methods for the discrimination of falls and blows, comprising three main indicators: the hat brim line rule, the side lateralization of fractures, and the number of lacerations. In the present study, we used the definition proposed previously by Kremer et al 5 : HBL corresponds to the area located between two lines parallel to a line inspired by the Frankfort horizontal plane (horizontal plane passing through right and left portion and the left orbitale), with the superior margin passing through the glabella (G line) and the inferior margin passing through the center of the external auditory meatus (EAM line).…”
Section: Discussionmentioning
confidence: 99%